Are changes in international accounting standards making them more complex? - Morais, Ana (2020)
One of the objectives of International Accounting Standards Board (IASB) is to develop high-quality standards based on clearly articulated principles. However, despite stating that International Financial Reporting Standards (IFRS) are based on principles, IASB continuously revises and amends IFRS. This paper explores the relation between the changes in IFRS and whether the standards have become more complex over time. The sample comprises changes to IFRS between 2005 and 2016. Following Mergenthaler [(2012). Principles-based versus rules-based standards and accounting irregularities (Working paper)] and Donelson, McInnis, and Mergenthaler [(2012). Rules-based accounting standards and litigation. The Accounting Review, 87(4), 1247–1279], this paper scores the rules-based continuum for each standard. The results show that IFRS is becoming more complex because of the changes